2009
DOI: 10.3810/pgm.2009.07.2019
|View full text |Cite
|
Sign up to set email alerts
|

Lansoprazole 15 mg Once Daily for 14 Days Is Effective for Treatment of Frequent Heartburn: Results of 2 Randomized, Placebo-Controlled, Double-Blind Studies

Abstract: During the 14-day treatment period in a population with frequent heartburn who were likely to select a medication without consulting a prescriber, lansoprazole 15 mg once daily showed rapid and sustained effectiveness throughout a 24-hour period and was well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 24 publications
2
22
0
Order By: Relevance
“…The mean percentage of 24-hour days without heartburn during 14 days of treatment was greater in subjects treated with lansoprazole than in placebo recipients (p<0.0001 vs. placebo for lansoprazole in each study) (Figure 2), with more subjects on lansoprazole reporting no heartburn on day one of treatment compared with placebo (15-mg group vs placebo, p≤0.0005; 30-mg group vs placebo, p=0.0004) [40]. Subjects treated with lansoprazole also experienced a higher mean percentage of nighttimes with no heartburn during the 14-day treatment period, compared with subjects on placebo (p<0.0001 for all doses vs placebo) (Figure 3) [41].…”
Section: Lansoprazole In the Treatment Of Acid-related Gastrointestinmentioning
confidence: 99%
See 4 more Smart Citations
“…The mean percentage of 24-hour days without heartburn during 14 days of treatment was greater in subjects treated with lansoprazole than in placebo recipients (p<0.0001 vs. placebo for lansoprazole in each study) (Figure 2), with more subjects on lansoprazole reporting no heartburn on day one of treatment compared with placebo (15-mg group vs placebo, p≤0.0005; 30-mg group vs placebo, p=0.0004) [40]. Subjects treated with lansoprazole also experienced a higher mean percentage of nighttimes with no heartburn during the 14-day treatment period, compared with subjects on placebo (p<0.0001 for all doses vs placebo) (Figure 3) [41].…”
Section: Lansoprazole In the Treatment Of Acid-related Gastrointestinmentioning
confidence: 99%
“…Results from three studies described demonstrated that oncedaily lansoprazole 15 mg was effective and had a good tolerability profile in the treatment of frequent, including nighttime, heartburn in a self-treating population. [40,41] The 15-mg dose of lansoprazole, the lowest effective dose for acid-related gastrointestinal disorder symptoms, was shown to be as effective as the 30-mg dose. [41].…”
Section: Place Of Lansoprazole In the Management Of Heartburnmentioning
confidence: 99%
See 3 more Smart Citations